The Open Access Effect: Transforming Collection Development Using Open Repositories - Bolaji Oladokun; Atanda Sambo; Mary Bassey; Rexwhite Enakrire (International Journal of Librarianship (IJoL), 2024)
This paper explores the transformative impact of the Open Access (OA) movement on collection development in academic libraries, emphasizing the role of open repositories. This paper employed a qualitative research method through a systematic literature review. To achieve these objectives, literature was sourced from multiple academic databases, including Google Scholar, Scopus, Universities' Open repositories, and Web of Science. Key findings indicate a significant increase in hybrid, Gold OA, and Green OA journals, enhancing accessibility to scholarly materials and democratizing knowledge. The integration of OA resources into library collections has facilitated broader access to academic works, enabling libraries to reallocate funds from expensive subscriptions to support OA initiatives and improve digital infrastructure. The study highlights the positive effects of open repositories on collaboration, innovation, and equitable information dissemination. However, it also addresses challenges such as sustainability, quality control, copyright compliance, and digital preservation. Future directions suggest enhancing interoperability, embracing emerging technologies, expanding inclusivity and accessibility, supporting open science and data sharing, and strengthening community engagement.